Evaluation Program in Handling Cities without Slum Settlements (Kotaku) in Sukabumi City - Alfian Dwi Cahya; Andi Mulyadi; Rizki Hegia Sampurna (Publik : (Jurnal Ilmu Administrasi), 2023)
This study focuses on evaluating the city program policy without slums (kotaku) in Sukabumi City. In evaluation theory there are indicators to regulate the course of the program or program implementation in a good and comprehensive manner by producing programs for reducing slums in cities without slums in the city of Sukabumi. The results of the study show six indicators, namely effectiveness, efficiency, adequacy, responsiveness, and accuracy in solving the problems of the city program without slums in Sukabumi City. In implementing the city program without slums in Sukabumi City, this program policy has not been fully realized 100% considering that the overall progress of implementing activities in Sukabumi City still has slum areas remaining. Economic, social and political environmental conditions have a significant effect on the performance of the KOTAKU program. High participation can increase the effectiveness of program implementation and support strong public policy sustainability related to the KOTAKU program which is the most important factor in program implementation so that it can produce significant changes.